2014
DOI: 10.1111/ans.12760
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Australian data in the Australasian Vascular Audit

Abstract: There is a need to increase compliance with vascular audit in Australia and data accuracy is acceptable but could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
(9 reference statements)
0
24
0
Order By: Relevance
“…However, the international analyses of threshold for iAAA repair, operative technique, and age at repair are not affected by these parameters. The participating registries are validated locally, with several showing excellent internal and external validity for AAA data, 2730 but no validation of the ICVR data set as a whole was possible. Some of the participating registries are center or region based and do not cover all AAA repairs for a particular population base, which limits the possibility for detailed epidemiological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the international analyses of threshold for iAAA repair, operative technique, and age at repair are not affected by these parameters. The participating registries are validated locally, with several showing excellent internal and external validity for AAA data, 2730 but no validation of the ICVR data set as a whole was possible. Some of the participating registries are center or region based and do not cover all AAA repairs for a particular population base, which limits the possibility for detailed epidemiological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010-2011, 69% of AAA repairs according to the Australian Institute of Health and Welfare (AIHW) and Australian Vascular Audit (AVA) data were repaired endovascularly. 17 We still perform the majority of aneurysms with open repair for several reasons. First, throughout this period we have had excellent OAR results with very low mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic surgery outcomes in the endovascular eraUnfortunately, despite repeated attempts to include all procedures in the AVA, the capture rate for open aortic surgery is 66% in Australia; however, validation has confirmed that the accuracy of data entry is excellent. 13 Thus, some AAA interventions performed in Australasia will not have been included in this audit and is a weakness in this study as there is a potential for bias. The attainment of complete participation remains a goal of the Society.…”
Section: Discussionmentioning
confidence: 99%